2017
DOI: 10.1186/s12885-017-3875-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-302b inhibits tumorigenesis by targeting EphA2 via Wnt/ β-catenin/EMT signaling cascade in gastric cancer

Abstract: BackgroundEphA2 is a crucial oncogene in gastric cancer (GC) development and metastasis, this study aims to identify microRNAs that target it and serve as key regulators of gastric carcinogenesis.MethodsWe identified several potential microRNAs targeting EphA2 by bioinformatics websites and then analyzed the role of miR-302b in modulating EphA2 in vitro and in vivo of GC, and it’s mechanism.ResultsOur analysis identified miR-302b, a novel regulator of EphA2, as one of the most significantly downregulated micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 50 publications
5
40
0
Order By: Relevance
“…27 YAP phosphorylation by tyrosine kinase c-Abl is a critical step in selective activation of proapoptotic genes in response to DNA damage. 8,11,12 In present study, we further confirm the role of EphA2 in GC growth and development, and find that the regulation of YAP by EphA2 is one of the major mechanisms underlying EphA2-driven GC development, progression and therapy resistance. The Eph receptor tyrosine kinases and their ligands called ephrins play important roles in various physiological and disease processes.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…27 YAP phosphorylation by tyrosine kinase c-Abl is a critical step in selective activation of proapoptotic genes in response to DNA damage. 8,11,12 In present study, we further confirm the role of EphA2 in GC growth and development, and find that the regulation of YAP by EphA2 is one of the major mechanisms underlying EphA2-driven GC development, progression and therapy resistance. The Eph receptor tyrosine kinases and their ligands called ephrins play important roles in various physiological and disease processes.…”
Section: Discussionsupporting
confidence: 83%
“…31 We and others have previously reported that EphA2 overexpression is associated with poor prognosis for GC patients and promotes the EMT and invasion of GC cells through the Wnt/β-catenin pathway. 8,11,12 In present study, we further confirm the role of EphA2 in GC growth and development, and find that the regulation of YAP by EphA2 is one of the major mechanisms underlying EphA2-driven GC development, progression and therapy resistance.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…At present, 2,588 mature human miRNAs have been detected in the human genome and are estimated to modulate the expression of >30% of all the protein-coding genes (11). Previously, miRNAs have been reported to be abnormally expressed in almost all types of human cancers (12)(13)(14). In addition, studies have indicated that numerous miRNAs are dysregulated in OSCC, including miRNA (miR)-433 (15), miR-195-5p (16), miR-27b (17) and miR-373-3p (18).…”
Section: Introductionmentioning
confidence: 99%